KESIAPSIAGAAN TUNANETRA TERHADAP BENCANA GEMPABUMI DAN TSUNAMI (Penelitian di UPTD Rumoh Seujahtera Beujroh Meukarya Aceh Besar) - Dzakiyul Mubarrak; Nazli Ismail; Taqwaddin Husin (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Visually impaired is essentially a disabled person whose sense of vision condition is not working properly, thus requiring special treatment in disaster management. This study aims to analyze the knowledge, attitude, information, and preparedness in earthquake and tsunami disaster mitigation at UPTD Rumoh Seujahtera Beujroh Meukarya Aceh Besar. This research used descriptive method with qualitative approach and purposive sampling technique. Data was collected from in-depth interview, observation, and document review. The research results showed that 1) The earthquake and tsunami disasters preparedness for visually impaired person in UPTD Rumoh Seujahtera Beujroh Meukarya Aceh Besar has not been maximized. The forms of preparedness needed for the visually impaired are the implementation of Standard Operating Procedures and improvement capacity education; 2) knowledge and attitude of the visually impaired person are adequate enough. Sources of the knowledge and attitudes are from family, institutional management, and community who cares for disability in the forms given through discussion and socialization.